You've reached Sam - Thao, Dustin (Wednesday Books, 2021)
Seventeen-year-old Julie fell in love with Sam the day she met him, and planned to attend college with him; but Sam died, and getting rid of his things, trying to erase him from her life is not working, so desperate to hear his voice one more time, Julie calls his cellphone expecting to hear his voicemail--but then Sam answers, and suddenly their cellphones become the living connection between them, a connection Julie finds impossible to let go.